Advancing Translational Research through Facility Design in Non-AMC Hospitals. (April 2013) - Pati, Debajyoti; Pietrzak, Michael P.; Harvey, Thomas E.; Armstrong, Walter B.; Clarke, Robert; Weissman, Neil J.; Rapp, Paul E.; Smith, Mark S.; Fairbanks, Rollin J.; Collins, Jeffrey M.G.
OBJECTIVE: This article aims to explore the future of translational research and its physical design implications for community hospitals and hospitals not attached to large centralized research platforms. BACKGROUND: With a shift in medical services delivery focus to community wellness, continuum of care, and comparative effectiveness research, healthcare research will witness increasing pressure to include community-based practitioners. METHODS: The roundtable discussion group, comprising 14 invited experts from 10 institutions representing the fields of biomedical research, research administration, facility planning and design, facility management, finance, and environmental design research, examined the issue in a structured manner. The discussion was conducted at the Washington Hospital Center, MedStar Health, Washington, D.C. CONCLUSIONS: Institutions outside the AMCs will be increasingly targeted for future research. Three factors are crucial for successful research in non-AMC hospitals: operational culture, financial culture, and information culture. An operating culture geared towards creation, preservation, and protection of spaces needed for research; creative management of spaces for financial accountability; and a flexible information infrastructure at the system level that enables complete link of key programmatic areas to academic IT research infrastructure are critical to success of research endeavors.